Exploring the Pathophysiology of Henoch-Schönlein Purpura (HSP): A Comprehensive Review - Himanshu Jain; Kuljeet Kaur (International Journal of Cell Biology and Cellular Functions, 2024)
Blood from tiny veins can leak into nearby tissues, causing purpura, a disorder marked by red spots or patches on the skin that may have an impact on the kidneys. Henoch-Schönlein purpura (HSP) is associated with vasculitis and inflammation of blood vessels. The range of renal conditions associated with purpura includes severe glomerulonephritis and mild proteinuria. For instance, immunological complex accumulation in the renal glomeruli of HSP patients might result in inflammation and renal injury. The pathophysiology of HSP is largely dependent on immunological pathways, including complement activation and immune complex deposition. Effective management of these renal symptoms depends on rapid identification and action. In addition to skin discoloration and renal involvement, purpura may present with other symptoms, including fatigue, joint pain, and mucosal bleeding. Though the precise etiology of HSP is unknown, it is thought to be related to an unbalanced immune system reaction that may be brought on by an infection or other circumstances. Treatment strategies depend on the underlying cause and may involve immunosuppressive therapy, plasmapheresis, or supportive care. For the most effective treatment for patients with HSP, a multidisciplinary strategy comprising gastroenterologists, nephrologists, and rheumatologists is recommended. Supportive treatment for gastrointestinal and renal disorders may include fluid replacement, pain relief, and, in certain situations, immunosuppressive medication. A long-term follow-up is necessary to evaluate renal function and keep an eye out for disease recurrence. This study aims to give a thorough overview of HSP, including information on its pathophysiology, diagnosis, possibilities for treatment, and clinical signs and symptoms.
Keywords: Henoch-Schönlein purpura (HSP); IgA vasculitis; Nephritic; anti-endothelial cell antibodies; galactose-deficient IgA1; renal disorder